1988
DOI: 10.1111/j.1467-8624.1988.tb03211.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific Intellectual Deficits in Children with Early Onset Diabetes Mellitus

Abstract: 27 children with early onset (less than 4 years) diabetes (EOD), 24 with late onset (greater than 4.0 years) diabetes (LOD), and 30 sibling controls were compared in their performance on tests of intellectual functioning and school achievement. The results indicated that children with EOD, particularly girls, scored lower than the other groups of diabetic children and siblings on tests of visuospatial but not verbal ability. Many of the children with EOD were also having difficulty at school, and a number were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
73
2

Year Published

1992
1992
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 29 publications
4
73
2
Order By: Relevance
“…In other cognitive ability studies of children with type 1 diabetes, EOD onset has been variously defined as occurring anywhere from age 4 to age 7 years (1), with little reference for preferences (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Magnetic resonance imaging (MRI) neurodevelopmental studies have demonstrated that adult brain volumes are attained by age 7-10 years (17).…”
Section: Definition Of Eodmentioning
confidence: 99%
See 1 more Smart Citation
“…In other cognitive ability studies of children with type 1 diabetes, EOD onset has been variously defined as occurring anywhere from age 4 to age 7 years (1), with little reference for preferences (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Magnetic resonance imaging (MRI) neurodevelopmental studies have demonstrated that adult brain volumes are attained by age 7-10 years (17).…”
Section: Definition Of Eodmentioning
confidence: 99%
“…Ack et al (1) first identified an association between early-onset type 1 diabetes (EOD) and comparatively lower general intelligence test scores; children with diabetes averaged 10 IQ points lower than their siblings. Subsequent studies identified small-tomoderate permanent differences in nonverbal (2)(3)(4)(5) and verbal (6) intelligence, information processing (3,(7)(8)(9), visuospatial ability (3)(4)(5), attention (7)(8)(9)(10)(11), executive function (7,9,12), and learning and memory ability (2,3,7). Prospective evaluation has confirmed that EOD independently influences verbal and nonverbal intelligence, attention, psychomotor speed, and executive functions (6,9).…”
mentioning
confidence: 99%
“…A second aim of the current study is to determine whether some children with type 1 diabetes have an elevated risk of cognitive dysfunction. Earlier age of diabetes onset is identified in the literature as one of the strongest risk factors associated with disrupted cognitive functioning (3,4,5,6). To examine the impact of early-onset diabetes (EOD) on cognitive abilities, a second meta-analysis is conducted to compare children classified by authors as having earlier age at onset, which may range anywhere from 4 to 7 years depending on the author, to later age at onset (late-onset diabetes [LOD]).…”
mentioning
confidence: 99%
“…5,14 However, these results have been contradictory; some studies have identified verbal and memory difficulties, whereas others have failed to find verbal difficulties and have instead identified visuospatial deficits. Neuropsychological deficits have been associated with a number of risk factors, most commonly onset of type 1 diabetes before the age of 7 5,7,10,11,15 and psychosocial factors such as increased school absences. 12,16 Ryan 17 noted that children with earlyonset diabetes tend to have spatial difficulties, whereas children with later onset have difficulties with verbal abilities, school achievement, and psychomotor skills.…”
mentioning
confidence: 99%